PENGARUH DURABILITAS TERHADAP DAYA DUKUNG STABILISASI TANAH MENGGUNAKAN LEMPUNG PLASTISITAS RENDAH DENGAN KAPUR - Idharmahadi Adha (UNIVERSITAS LAMPUNG, 2009)
Structure pavement in highway engineering which applicated soil stabilization method as basecourse, floating of water was a problem must be controlled. Lime is one of natural material couldbe used as additive in soil stabilization. Lime will reduce soil plasticity, increase strength anddurability, decrease water absorption ang swelling soils. To design. soil lime stabilization as basecourse, will be used clay material in low plasticity. To know influence of durability for floating ofwater in laboratory test is used by cycle periodic. Based on research that bearing capacity ofsoil lime base, the value of CBR laboratory at fourth cycle is 98 % (less than 100 %). By thiscondition, if soil lime base construction wiil be floating by water every year in rainy seasion, atfourth year, soil lime base could not accomplish technical spesifications., minimize of CBR valueis 100 %. The conclusion is floating of water will decrease bearing capacity of soil lime base andincrease soil plasticity properties